2015
DOI: 10.1134/s1990750815020080
|View full text |Cite
|
Sign up to set email alerts
|

AFM-based protein fishing in the pulsed electric field

Abstract: A combination of (atomic force microscopy) based fishing (AFM fishing) and mass spectrometry allows to capture protein molecules from solutions, concentrate and visualize them on an atomically flat sur face of the AFM chip and identify by subsequent mass spectrometric analysis. In order to increase the AFM fishing efficiency we have applied pulsed voltage with the rise time of the front of about 1 ns to the AFM chip. The AFM chip was made using a conductive material, highly oriented pyrolytic graphite (HOPG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Another factor influencing the protein fishing efficiency (as is indicated by the results obtained in this study and in ) is an external electric field. To provide the detection efficiency, pulsed electrical stimulation of AFM‐based fishing is required.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Another factor influencing the protein fishing efficiency (as is indicated by the results obtained in this study and in ) is an external electric field. To provide the detection efficiency, pulsed electrical stimulation of AFM‐based fishing is required.…”
Section: Discussionmentioning
confidence: 71%
“…Earlier in our studies [5,12] we have shown that the concentration of proteins on the surface may be attained without turbulent stirring or high-strength fields. We have shown [5] that the concentration is more efficient upon the fast (injection) input of protein solution into the measuring cell.…”
mentioning
confidence: 57%
See 3 more Smart Citations